2020
DOI: 10.32604/cmc.2020.013125
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Lumbar Implant and Diagnosing Scoliosis from Vietnamese X-Ray Imaging Using the Pre-Trained API Models and Transfer Learning

Abstract: With the rapid growth of the autonomous system, deep learning has become integral parts to enumerate applications especially in the case of healthcare systems. Human body vertebrae are the longest and complex parts of the human body. There are numerous kinds of conditions such as scoliosis, vertebra degeneration, and vertebrate disc spacing that are related to the human body vertebrae or spine or backbone. Early detection of these problems is very important otherwise patients will suffer from a disease for a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The suggested model was tested on a dataset of lung cancer by scientists, and the model reported accuracy of 0.97. Another study [ 43 ] suggested three different CNN models to classify the coronavirus contamination in X-radiation cases, including Inception-ResNetV2, InceptionV3, and ResNet50. In terms of detection and identification, the ResNet50 system outperformed InceptionV3 and Inception-ResNetV2 with 0.98 accuracy, whereas InceptionV3 attained 0.97, and Inception-ResNetV2 attained 0.87.…”
Section: Related Workmentioning
confidence: 99%
“…The suggested model was tested on a dataset of lung cancer by scientists, and the model reported accuracy of 0.97. Another study [ 43 ] suggested three different CNN models to classify the coronavirus contamination in X-radiation cases, including Inception-ResNetV2, InceptionV3, and ResNet50. In terms of detection and identification, the ResNet50 system outperformed InceptionV3 and Inception-ResNetV2 with 0.98 accuracy, whereas InceptionV3 attained 0.97, and Inception-ResNetV2 attained 0.87.…”
Section: Related Workmentioning
confidence: 99%